Manhaǧ al-Imām al-Ḫumainī fi 't-tafsīr - Zain-al-ʿĀbidīn, ʿAbd-as-Salām (Dār al-Hādī li-'ṭ-Ṭibāʿa wa-'n-Našr wa-'t-Tauzīʿ, 2001)
Khomeini, Ruhollah; contributions in; Koran; hermeneutics
Keywords: Khomeini; Ruhollah / Views on hermeneutics; Khomeini; Ruhollah; Ḫumainī; Rūḥallāh Mūsawī; Qurʼan / Hermeneutics; Qurʼan; Hermeneutics; Hermeneutik; Tafsir